Rokan Hulu Ulama's Views on the Appointment of Parents as a Condition of Malay Traditional Marriage - Tanjung, Dai Robi; Turnip, Ibnu Radwan Siddik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to find out the tradition of appointing parents of the same family as a condition of Malay traditional marriage and to find out how the Rokan Hulu Ulama views on the tradition. This research is designed with a qualitative method to be able to explain in as much detail as possible about the appointment of parents of the same family as a condition of Malay traditional marriage. This research is a normative-empirical research with a sociological approach. Primary data sources are obtained from interviews with several respondents, while secondary data sources are obtained from several references that explain the tradition of the appointment of surname parents as a condition of Malay traditional marriage in Rokan Hulu. While the analysis technique is descriptive. The results of this study found that the Rokan Hulu ulama did not approve of the appointment of semarga parents as a condition of marriage. Based on the results of this study, the author concludes that the Rokan Hulu scholars agreed to disagree with the appointment of parents of the same family as a condition of marriage because it contradicts the law of shara' and makes it difficult for someone who wants to get married, then this tradition only applies in the Rokan Hulu area and does not apply universally to Muslims so it deserves to be disapproved by the scholars.